Analysis of VO2MAX Differences between Laboratory Test and Field Test in Rowing - Angga Muhammad Syahid (JURNAL PENDIDIKAN JASMANI DAN OLAHRAGA, 2021)
The purpose of this study was to analyze the results of VO2max measurement using laboratory test and field test. This research is a descriptive quantitative research with a comparative approach. The samples of this study were 30 male and female athletes of the Indonesian rowing team (male = 17, female = 13) aged 23.5 ± 3.5 years. The anthropometric profile of the athletes included height = 182.2 ± 5.01 cm for male and 171.9 ± 5.73 cm for female, weight = 74.2 ± 5.85 kg for male and 68.6 ± 8.5 kg for female. According to the results of analysis of VO2max rowing test data gained from both methods, there were low and moderate correlations in the laboratory test and field test in rowing (male r = 0.425 and female r = 0.62). The results show that VO2max measured in the laboratory test and field test did not show a significant difference. Therefore, these two parameter tests can be used in Vo2Max testing.